Biosynthesis of Poly (3-Hydroxybutyrate-Co-3-Hydroyvalerate) Copolymer from Organic Acids Using Comamonas sp. EB172 - Zakaria @ Mamat, Mohd Rafein (2011)
Petroleum-based plastics like polypropylene (PP) and polyethylene (PE) are common plastics used in our daily life. Despite having good thermal and mechanical properties which make these plastics suitable for wide range applications, they are non-biodegradable and their accumulation has resulted in environmental concern by consumers all round the world. Polyhydroxyalkanoates (PHAs) have been recognized as suitable candidates in replacing partially or completely petroleumbased plastics since they share similar thermal and mechanical properties. Moreover, the biodegradability aspect of PHA makes these polymers to be more desirable and environmental friendly. Nevertheless, the total PHAs production cost is more expensive in comparison to conventional plastics, a factor that limits the production of these materials in large scale. The use of a locally- isolated bacterial species that can convert organic acids derived from anaerobically treated palm oil mill effluent (POME) with an efficient fermentation process will help to reduce the total PHA production cost. In this study, isolation and screening of PHA producing bacterium was performed by using Nile Blue A staining method. The stained colonies containing PHA exhibited pink fluorescent colour when exposed under ultra violet (UV) light. The PHA producing bacterium obtained from digester- treated POME was characterized by polyphasic taxonomic approach. The cells were rod-shaped, Gramnegative, non-pigmented, non-spore-forming and non-fermentative. Phylogenetic analyses using the 16S rRNA gene sequence showed that the isolate was clustered in the genus of Comamonas. Thus Comamonas sp. EB172 is designated for the locally isolated bacterial species. Its closest neighbours are the type strains Comamonas terrigena (96.8%), Comamonas koreensis (93.4%), Comamonas composti (92.9%) and Comamonas kerstersii (91.1%). Comamonas sp. EB172 was clearly distinguished from all of the existing Comamonas species using phylogenetic analysis, fatty acid composition and a range of physiological and biochemical characteristics. The G+C content of the genomic DNA was 59.1 mol%. It is evident from the genotypic, phenotypic data and ability to produce PHA that Comamonas sp.EB172 represents a new species in the genus Comamonas (GeneBank accession no.EU847238). Based on the types of carbon sources tested in shake flasks experiments, poly(3-hydroxybutyrate) [P(3HB)] homopolymer and poly(3-hydroxybutyrate-co-3-hydroxyvalerate) [P(3HB-co-3HV)] copolymer were produced by Comamonas sp.EB172 using single and mixed carbon sources. Poly(3-hydroxyvalerate) P(3HV)incorporation in the copolymer was obtained when propionic and valeric acid were used as precursors. Incorporation of 3HV fractions in the copolymer varied from 45 to 86 mol% when initial pH of the medium was regulated. In fed-batch cultivation, organic acids derived from anaerobically treated POME which consist mainly acetic, propionic and butyric acids are shown to be suitable carbon sources for polyhydroxyalkanoate (PHA) production by Comamonas sp. EB172. The number average molecular weight (Mn) of P(3HB-co-3HV) copolymer produced by the strain was in the range of 153 to 412 kDa with polydispersity index (Mw/Mn) in the range of 2.2 to 2.6. Incorporation of higher 3HV units improved the thermal stability of P(3HB-co-3HV) copolymer. The CDW (14.6 g/L) and the Mn (838 x 103 Da) of P(3HB-co-3HV) copolymer reached the highest when supplemented with yeast extract during the fermentation period. Tensile strength, elongation to break and Young`s modulus of the copolymer containing 6-8 mol% P(3HV) were recorded at 12-15 MPa, 160-710% and 0.19-0.34 GPa respectively. Thus the newly isolated bacterium Comamonas sp. EB172 is shown to be a suitable candidate for PHA production using organic acids from POME as a renewable and alternative raw material